Quantification of Reduction in Hydraulic Conductivity and Skid Resistance Caused by Fog Seal in Low-Volume Roads. Issue 1 (January 2017) - Islam, Readul Mohammad; Arafat, Shams; Wasiuddin, Nazimuddin M.
Fog seal increases pavement life and postpones major rehabilitation. The reduction of permeability caused by fog sealing will reduce moisture-induced damage, but this benefit comes with a temporary loss of surface friction. However, quantifying the effectiveness of fog sealing by measuring permeability is a difficult task. Although fog seal may be a good low-cost maintenance option for low-volume roads, the rate of recovery of friction may be very slow because of less rubbing action between the fog-sealed surface and tires. Four low-volume parish roads in Caddo Parish, Louisiana, were selected for this study. Two emulsions, CSS-1H and E-Fog, with three application rates, were used to evaluate the reduction in hydraulic conductivity and to assess the characteristics of friction over time. Results showed that fog seal can be expected to be fully cured within 2.5 to 3.5 hours for an application rate of 0.2 to 0.4 gallons per square yard (gal/yd 2 ). The same field cores were tested before and after fog sealing to quantify exactly the reduction in hydraulic conductivity. It was observed that fog seal has a significant potential to reduce hydraulic conductivity. Considering all four pavements and application rates of 0.1 to 0.22 gal/yd 2, the average reduction in hydraulic conductivity was 38.5%. Reduction in hydraulic conductivity shows very slight sensitivity to the application rate. Irrespective of road type, emulsion, and application rate, fog seal causes a sudden drop in the International Friction Index parameter F60 by 20% to 40%. A fog-sealed surface does not return to the original level of friction after three months; however, the rate of recovery was the highest for the busiest of the observed Caddo Parish roads.